2004
DOI: 10.1093/nar/gkh671
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific and imprinted epigenetic modifications of the human NDN gene

Abstract: Allele-specific DNA methylation, histone acetylation and histone methylation are recognized as epigenetic characteristics of imprinted genes and imprinting centers (ICs). These epigenetic modifications are also used to regulate tissue-specific gene expression. Epigenetic differences between alleles can be significant either in the function of the IC or in the cis-acting effect of the IC on 'target' genes responding to it. We have now examined the epigenetic characteristics of NDN, a target gene of the chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 49 publications
5
39
0
Order By: Relevance
“…Although we identified necdin to be upstream of Wnt, how other preadipocyte-selective or anti-adipogenic genes regulate necdin expression in HSCs, is unknown at the present time. Of equal importance is epigenetic regulation of necdin via paternal allelespecific histone acetylation, which appears to contribute to tissue-specific activity (36). In summary, our study has identified necdin as a new regulator for the cell fate of HSCs.…”
mentioning
confidence: 71%
“…Although we identified necdin to be upstream of Wnt, how other preadipocyte-selective or anti-adipogenic genes regulate necdin expression in HSCs, is unknown at the present time. Of equal importance is epigenetic regulation of necdin via paternal allelespecific histone acetylation, which appears to contribute to tissue-specific activity (36). In summary, our study has identified necdin as a new regulator for the cell fate of HSCs.…”
mentioning
confidence: 71%
“…To study how PWS-IC activates the genes on the paternal allele across the PWS/AS domain, we chose NDN as a representative gene, which is monoallelically expressed mainly in brain (11), being simple, intronless, and a member of the upstream PEG cluster, which includes NDN, MKRN3, and MAGEL2, and is believed to be a target of the PWS-IC activating function (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…To discriminate between the maternal and paternal alleles, we used lymphoblasts from a Prader-Willi patient and his father, who carried a deletion in their PWS-IC on one chromosome (PWS-U family) and from an Angelman patient and his mother, who were deleted in AS-IC (AS-D family). Although NDN is not expressed in these lymphoblasts, it is differentially methylated (11). Chromatin of these lymphoblast cells was subjected to the 3c procedure (SI Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…We established 11 assays based on literature review [22][23][24][25][26][27][28][29] , as shown in Supplementary Table S2. We failed to establish a reliable bisulphite pyrosequencing assay for the KvDMR/IC2 in 11p15.…”
Section: Bisulphite Pyrosequencingmentioning
confidence: 99%